Complete regression of breast tumour with a single dose of docetaxel-entrapped core-cross-linked polymeric micelles. (June 2015) - Hu, Qizhi; Rijcken, Cristianne J.; Bansal, Ruchi; Hennink, Wim E.; Storm, Gert; Prakash, Jai
Abstract: Treatment with chemotherapy such as docetaxel (DTX) is associated with significant toxicity and tumour recurrence. In this study, we developed DTX-entrapped core-cross-linked polymeric micelles (DTX-CCL-PMs, 66 nm size) by covalently conjugating DTX to CCL-PMs via a hydrolysable ester bond. The covalent conjugation allowed for sustained release of DTX under physiological conditions in vitro . In vivo, DTX-CCL-PMs demonstrated superior therapeutic efficacy in mice bearing MDA-MB-231 tumour xenografts as compared to the marketed formulation of DTX (Taxotere ® ). Strikingly, a single intravenous injection of DTX-CCL-PMs enabled complete regression of both small (∼150 mm 3 ) and established (∼550 mm 3 ) tumours, leading to 100% survival of the animals. These remarkable antitumour effects of DTX-CCL-PMs are attributed to its enhanced tumour accumulation and anti-stromal activity. Furthermore, DTX-CCL-PMs exhibited superior tolerability in healthy rats as compared to Taxotere. These preclinical data strongly support clinical translation of this novel nanomedicinal product for the treatment of cancer.